Effect of Chilled Storage on Antioxidant Capacities and Volatile Flavors of Synbiotic Yogurt Made with Probiotic Yeast Saccharomyces boulardii CNCM I-745 in Combination with Inulin - Abid Sarwar; Sam Al-Dalali; Tariq Aziz; Zhennai Yang; Jalal Ud Din; Ayaz Ali Khan; Zubaida Daudzai; Quratulain Syed; Rubina Nelofer; Nazif Ullah Qazi; Zhang Jian; Anas S. Dablool (Journal of Fungi, 2022)
Fermentation of available sugars in milk by yogurt starter culture initially and later by Saccharomyces boulardii (Probiotic yeast) improves the bioavailability of nutrients and produces bioactive substances and volatile compounds that enhance consumer acceptability. The combination of S. boulardii, a unique species of probiotic yeast, and inulin, an exopolysaccharide used as a prebiotic, showed remarkable probiotic and hydrocolloid properties in dairy products. The present study was designed to study the effect of fermentation and storage on antioxidant and volatile capacities of probiotic and synbiotic yogurt by incorporation of S. boulardii and inulin at 1%, 1.5%, and 2% (w/v), compared with the probiotic and control plain yogurt. All samples were stored at 4 °C, and during these four weeks, they were analyzed in terms of their antioxidant and volatile compounds. The synbiotic yogurt samples having inulin and S. boulardii displayed significantly higher DPPH (2,2-diphenyl-1-picrylhydrazyl) free radical activity values and more values of TPC (total phenol contents) than control plain yogurt. A total of 16 volatile compounds were identified in S5-syn2 and S4-syn1.5, while S3-syn1 and S2-P had 14, compared with the control S1-C plain yogurt samples, which had only 6. The number of volatile compounds increased with the increasing concentration of inulin throughout the storage period. Therefore, this novel synbiotic yogurt with higher antioxidant and volatile compounds, even with chilling storage conditions, will be a good choice for consumer acceptability.